TEACHERS’ PERSPECTIVES ON TEACHING AND LEARNING STRATEGIES IN UNDERGRADUATE ENGINEERING COURSES - Viacelli da Luz, Samoara; Moreira, Herivelto (Advances in Social Sciences Research Journal, 2018)
The objective of this article was to identify what are the teaching strategies most used by teachers of undergraduate engineering courses from three campus of a public university in southern Brazil. The concepts used were based on studies conducted by numerous national and international authors in higher education pedagogical area, and specifically in engineering education. The literature proposes several teaching strategies which allow student’s active participation, autonomy, the ability to discuss and solve problems, among other characteristics necessary for the future engineer, in order to overcome a teacher-centered approach focused on memorization. The research methodology used was a mixed sequential explanatory design that consisted of two distinct phases: a first phase with a quantitative approach and a second phase with a qualitative approach. The main results show that “lectures” are still the most used teaching strategies. In relation to the other teaching strategies proposed in the literature, the teachers demonstrated different forms of understanding and application, making it difficult to verify the frequency of use.